2020
DOI: 10.18662/rrem/12.1sup2/258
|View full text |Cite
|
Sign up to set email alerts
|

Quarantine: Teaching English From Home With Google Classroom, Classtime and Quizlet

Abstract: Quarantine created the environment where educators and students have to teach and learn being socially isolated. The paper reports the results of distance learning realized by integration of Google Classroom, Classtime and Quizlet. The authors present the results of the survey based on a 10-item 5point Likert scale which was proposed to the learners after one month of distance learning in quarantine conditions at National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute". A mixed metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…This study is a modest contribution to the ongoing discussions about the efficiency of different aspects of e-learning mode of instructing future translators and interpreters, especially in forming their terminological competence in bilateral interpreting, during the pandemic process. Our results are in good agreement with other studies (Adams Becker et al, 2017;Alcina, 2011;Antón, 2016;Lukianenko & Vadaska, 2020;Saienko & Chugai, 2020;Sikora, 2014) which have shown that terminology-content assignments on the basis of through computer-mediated instruction can substantially improve the quality and efficiency of the educational process.…”
Section: Discussionsupporting
confidence: 93%
“…This study is a modest contribution to the ongoing discussions about the efficiency of different aspects of e-learning mode of instructing future translators and interpreters, especially in forming their terminological competence in bilateral interpreting, during the pandemic process. Our results are in good agreement with other studies (Adams Becker et al, 2017;Alcina, 2011;Antón, 2016;Lukianenko & Vadaska, 2020;Saienko & Chugai, 2020;Sikora, 2014) which have shown that terminology-content assignments on the basis of through computer-mediated instruction can substantially improve the quality and efficiency of the educational process.…”
Section: Discussionsupporting
confidence: 93%
“…al, (2018), menyatakan kebanyakan guru mempunyai pengetahuan asas komputer, namun kurang mahir dalam menyediakan bahan-bahan pembelajaran digital. Manakala, kajian Saienko et al (2020) turut menyatakan bahawa guru-guru yang tidak mempunyai kemahiran teknikal yang mencukupi akan merasa tertekan dalam mengendalikan Google Classroom. Kajian Rahmi et al ( 2019) menyatakan latihan dapat mendorong guru meningkatkan pengetahuan serta kefahaman berkaitan proses pembangunan (Learning Management System) LMS-Google Classroom, guru dapat membuat LMS-Google Classroom sehingga memuat naik bahan pengajaran dan penilaian menggunakan Google Form, serta guru mampu meningkatkan ketrampilan dalam mengintegrasikan teknologi dalam proses pengajaran menggunakan LMS-Google Classroom.…”
Section: Kesediaan Guruunclassified
“…The biggest issues that students saw with online learning were miscommunication (34%) and lack of information (34%). Poor or unstable Internet connection was the next biggest issue (29%) [12]. Online education tools such as 'Google Classroom' provide a platform to store lecture recordings, submit assignments, and provide grading feedback.…”
Section: Challenges Of Blended Learningmentioning
confidence: 99%
“…Online education tools such as 'Google Classroom' provide a platform to store lecture recordings, submit assignments, and provide grading feedback. Though they lack direct communication between faculty and students, utilizing 'Skype' or 'Zoom' can compensate for that loss [12].…”
Section: Challenges Of Blended Learningmentioning
confidence: 99%